Role of bi‐weekly serum galactomannan screening for the diagnosis of invasive aspergillosis in haematological cancer patients. Issue 6 (14th March 2018) - Couchepin, Jade; Brunel, Anne‐Sophie; Jaton, Katia; Meylan, Pascal; Bochud, Pierre‐Yves; Lamoth, Frédéric
Summary: Invasive aspergillosis (IA) is a life‐threatening infection affecting haematological cancer patients with chemotherapy‐induced neutropenia. The diagnosis of IA often relies on the detection of galactomannan (GM) in serum or bronchoalveolar lavage fluid (BAL). Bi‐weekly serum GM screening has been proposed for a pre‐emptive therapeutic approach of IA in patients not receiving mold‐active prophylaxis. We have analysed all IA cases among patients with haematological malignancies and prolonged chemotherapy‐induced neutropenia (>14 days) in our institution over a 10‐year period (2007‐2017). Serum GM was measured twice weekly and mold‐active prophylaxis was not routinely administered. Thirty IA cases were observed and a positive serum GM was the first indicator of IA in 10 (33%) of them, which represents a need of approximately 500 GM tests for the detection of a single IA case. In the other 20 (67%) cases, suggestive chest CT lesion was the first sign of IA and bronchoscopy was required in 15 (50%) cases with negative serum GM for establishing the diagnosis of probable/proven IA. A positive serum GM was associated with a worse prognosis (57% 12‐week survival vs 100% among serum GM‐negative patients, P  = .006), irrespective of the timing of GM positivity compared to CT. We concluded that bi‐weekly serum GM screening demonstrated limited benefit in this population.